Drosophila Y14 shuttles to the posterior of the oocyte and is required for oskar mRNA transport. - Hachet, O.; Ephrussi, A. (Current Biology, 2001)
mRNA localization is a powerful and widely employed mechanism for generating cell asymmetry. In Drosophila, localization of mRNAs in the oocyte determines the axes of the future embryo. oskar mRNA localization at the posterior pole is essential and sufficient for the specification of the germline and the abdomen. Its posterior transport along the microtubules is mediated by Kinesin I and several proteins, such as Mago-nashi, which, together with oskar mRNA, form a posterior localization complex. It was recently shown that human Y14, a nuclear protein that associates with mRNAs upon splicing and shuttles to the cytoplasm, interacts with MAGOH, the human homolog of Mago-nashi.Here, we show that Drosophila Y14 interacts with Mago-nashi in vivo. Immunohistochemistry reveals that Y14 is predominantly nuclear and colocalizes with oskar mRNA at the posterior pole. We show that, in y14 mutant oocytes, oskar mRNA localization to the posterior pole is specifically affected, while the cytoskeleton appears to be intact.Our findings indicate that Y14 is part of the oskar mRNA localization complex and that the nuclear shuttling protein Y14 has a specific and direct role in oskar mRNA cytoplasmic localization.